Предмет: Алгебра,
автор: 111111DA
Не знаю,как решить,весь день решаю!!!
Упростить выражение,при a>0,b>0:
Приложения:
Ответы
Автор ответа:
2
a) a⁻³*∛(a⁶b²)/∛b=a⁻³*∛(a⁶b²/b)=a⁻³*∛(a⁶b)=a⁻³*a²*∛b=a⁻¹*∛b=∛b/a.
б)
1. (1/(a^(√2-1))^(√2+1)=(a^(1-√2))^(1+√2)=a^(1²-(√2)²)=a^(1-2)=a^(-1),
a^(-1)*a(√2+1)=a^(-1+√2+1)=a^(√2).
Похожие вопросы
Предмет: Английский язык,
автор: znando45
Предмет: Математика,
автор: golubevavika1905
Предмет: Русский язык,
автор: MerkisKhalitov
Предмет: Математика,
автор: pil1
Предмет: Алгебра,
автор: ruslangorba4yow